Silvopasture for improved smallholder crop-livestock systems: A case study of sustainable intensification in the Xieng Khouang province, Lao PDR - van Wijngaarden, Kim; Cossu, Alessandra; Jalonen, Riina; Atieno, Mary; Ritzema, Randall; López Ridaura, Santiago; Groot, Jeroen C.J. (International Maize and Wheat Improvement Center, 2023)
The Lao People's Democratic Republic has experienced significant changes in agricultural development and commercialization over the past few decades. Approximately 80% of its population relies heavily on subsistence agriculture. These farmers have witnessed a remarkable decrease in the poverty rate, dropping from 46% to 18% between 1993 and 2019. This positive transformation can be attributed to enhanced infrastructure, enabling farmers to access markets in neighboring countries. Additionally, a considerable upswing in the livestock sector has occurred due to increased demand, particularly from China for export, and a heightened need for cash crops from the Vietnamese market.